A "Chariot of Fire" in Amos 7:4: A Text Critical Solution for qōrē' lārīb bā'ēš. - Simone, Michael R. (Vetus Testamentum, 2016)
MT Amos 7:4 has a number of difficulties, one of which is the phrase qōrē’ lārīb bā’ēš. Although all ancient versions agree in some way with the Hebrew, differences among them reveal the difficulty that ancient scholars encountered when interpreting the phrase. The difficult Hebrew and the multiple ancient versions together have led many modern scholars to attempt an emendation. The textual corrections suggested by Hendrik Elhorst and Delbert Hillers appear in important English biblical translations, but both are problematic. This study suggests the emendation qōrē’ lǝrekeb ’ēš as a solution to the crux. The initial error was caused by misdivision of words coupled with bet-kaf confusion. Unlike the other suggestions, this correction has three strengths to recommend it: the error was simple, the corrected words appear elsewhere in Hebrew, and the image of a fiery divine chariot has counterparts in cognate ancient Near Eastern literature.